2001
DOI: 10.1002/cne.1141
|View full text |Cite
|
Sign up to set email alerts
|

Injury‐induced apoptosis of neurons in adult brain is mediated by p53‐dependent and p53‐independent pathways and requires bax

Abstract: The mechanisms of injury-induced apoptosis of neurons within the CNS are not understood. We used a model of cortical injury in rat and mouse to induce retrograde neuronal apoptosis in thalamus. In this animal model, unilateral ablation of the occipital cortex causes unequivocal apoptosis of corticopetal projection neurons in the dorsal lateral geniculate nucleus (LGN) by 7 days postlesion. We tested the hypothesis that p53 and Bax regulate this retrograde neuronal apoptosis. We found, by using immunocytochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
50
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 55 publications
(103 reference statements)
9
50
0
Order By: Relevance
“…P53 mediates apoptosis (Benchimol, 2001;Shen and White, 2001;Martin et al, 2001;Liu et al, 2013). Previous studies have demonstrated p53 overexpression in PD brain (De La Monte et al, 1998;Mogi et al, 2007;Da Costa et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…P53 mediates apoptosis (Benchimol, 2001;Shen and White, 2001;Martin et al, 2001;Liu et al, 2013). Previous studies have demonstrated p53 overexpression in PD brain (De La Monte et al, 1998;Mogi et al, 2007;Da Costa et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Sections were selected with a random start and systematically sampled (every ninth section) to generate a subsample of sections from each mouse lumbar spinal cord that were mounted on glass slides and stained with cresyl violet for neuronal counting. Neuronal counts in the ipsilateral and contralateral ventral horns were made at 1000ϫ magnification using the stereological optical disector method as described previously (Calhoun et al, 1996;Martin et al, 1999). MNs without apoptotic structural changes were counted using strict morphological criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Phosphorylated p53 was detected with a rabbit antibody to serine-15 phosphorylated p53 (Cell Signaling). The specificities of these antibodies were evaluated by immunoblotting or have been evaluated previously (Northington et al, 1996;Martin et al, 2001;Martin and Liu, 2002a;Graham et al, 2004). Negative control sections were incubated in comparable dilutions of IgG or with the primary or secondary antibody omitted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations